MANAJEMEN PENGEMASAN SKEMA OKUPASI PADA LEMBAGA SERTIFIKASI PROFESI PIHAK KEDUA DI BALAI BESAR PENGEMBANGAN PENJAMINAN MUTU PENDIDIKAN VOKASI SENI DAN BUDAYA - Haryadi Purnomo Raharjo (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The occupational certification scheme is a certification based on a work position in an industrialsystem that has been determined nationally. The occupational certification scheme was initiatedin response to the dynamics of industrial needs. The occupational certification scheme is an effortto connect the world of education with the real needs of industry. As an effort to align vocationaleducation with the needs of the world of work, the preparation of this scheme was carried outwith collaboration and active participation from various related parties. This occupationalcertification scheme is not only intended to increase the competitiveness of teachers andvocational education personnel, but also an effort to increase the opportunities for vocationaleducation graduates entering the job market in ease. In order to gain the recognition ofcompetency, the seamless implementation of competency certification, and references fordeveloping training curricula; the determination of the occupational set for arts and cultureteachers and vocational education staff is highly important and strategic. In order to arrangethis occupational scheme set, a management process is needed to integrate several groups ofactivities that are integrally related into occupational set. Skema sertifikasi okupasi adalah sertifikasi yang berdasarkan suatu jabatan kerja pada sistemindustri yang sudah ditetapkan secara nasional. Skema sertifikasi okupasi diinisiasi sebagairespons terhadap dinamika kebutuhan industri. Skema sertifikasi okupasi sebagai upaya untukmenghubungkan dunia pendidikan dengan kebutuhan riil industri. Sebagai upaya penyelarasanpendidikan vokasi dengan kebutuhan dunia kerja, penyusunan skema ini dilakukan dengankolaborasi dan partisipasi aktif dari berbagai pihak terkait. Skema sertifikasi okupasi ini tidakhanya untuk meningkatkan daya saing guru dan tenaga kependidikan vokasi, tetapi juga upayameningkatkan peluang lulusan pendidikan vokasi agar lebih lancar dalam memasuki pasar kerjayang terus berkembang. Dalam rangka pengakuan kompetensi, kelancaran pelaksanaansertifikasi kompetensi dan acuan bagi pengembangan kurikulum pelatihan maka penetapanpengemasan okupasi bagi guru dan tenaga kependidikan vokasi bidang seni dan budaya sangatlahpenting dan strategis. Dalam menyusun pengemasan skema okupasi ini, perlu proses manajemenuntuk mengintegrasikan beberapa gugusan kegiatan yang berhubungan secara integral menjadikemasan okupasi.